Cartas em tempos de guerra: a Revolução Federalista na correspondência recebida por Floriano Peixoto (1893-1894) - Gaspar, Waleska Sheila (2019)
The Federalist Revolution, as the civil war that took place between 1893 and 1895 in Rio Grande do Sul became known, opposed federalists and republicans in the struggle for the power of the State, and it integrates one of the most critical episodes that the newly proclaimed Republic of Brazil had to face. The conflict was not limited to the state of Rio Grande do Sul, reaching its neighboring states: Santa Catarina and Paraná. Therefore, the present study aims to analyze the Revolution from a documental set constituted by the passive correspondence during the revolt of the then president of the Republic Floriano Peixoto. In order to do so, a selection of the letters corresponding to the states that were directly involved in the conflict: Rio Grande do Sul, Santa Catarina and Paraná, was done as a means to understand the political influences due to the conflict from its regional perspective, as well as the relations that were established with the federal government in this concern. The analysis and interpretation of the letters refers to the theoretical-methodological references, which take into account the peculiarities of the epistolary writing, articulating to it studies that go through the identification of the document as the bearer of a discourse. Thus, it is important to understand the Federalist Revolution in its context taking into account its developments in the southern states in line with the participation of the federal government in the war, in search for characterizing the actions, political articulations, interests and ideas expressed in the investigated correspondence. The analysis of the sources shows the existence of a plot established between the individuals through the practices and discourses present in their correspondences, and these documents, besides revealing the perceptions, strategies and difficulties faced during the war, evidence the common values and ideals shared by the subjects in this specific historical context. In this way, this study contributes to the originality of the research, since the systematic investigation of the sources listed is something not yet presented in other examinations on the Federalist Revolution. Thereby, this paper contributes significantly to the historiography of the southern conflict and the political scenario that characterized the early years of the Brazilian Republic.